Effects of brine concentration and curing time on the sensory attributes and acceptability of salted quail eggs - Maglangit, Aries Jan F.
The combined effect of brine concentration and curing time on the sensory attributes (color of both egg yolk, taste, texture) and acceptability of salted quail eggs were investigated.